Gut microbiota in hypothyroidism: pathogenic mechanisms and opportunities for precision microbiome interventions - Jiang, Tao; Yang, Xiuqing; Wu, Baihui; Tao, Runchao; Chen, Rongbing; Jin, Libo; Sun, Da; Weng, Huibin (Frontiers in Microbiology, 2025)
Hypothyroidism is a common endocrine disorder characterized by insufficient thyroid hormone synthesis or secretion, most frequently caused by Hashimoto’s thyroiditis, an autoimmune condition that leads to chronic thyroid gland damage. Despite the widespread use of levothyroxine replacement therapy, a substantial proportion of patients continue to experience persistent symptoms and metabolic dysregulation even after achieving biochemical euthyroidism. These observations have prompted growing interest in non-hormonal contributors to hypothyroidism, particularly the role of the gut microbiota. Recent studies indicate that gut microbial dysbiosis may influence the onset and progression of hypothyroidism through mechanisms involving immune dysregulation, increased intestinal permeability, chronic low-grade inflammation, and impaired nutrient absorption. Additionally, microbial metabolites such as short-chain fatty acids and bile acids are increasingly recognized as modulators of thyroid hormone metabolism, tissue sensitivity, and enterohepatic circulation. The bidirectional interactions between thyroid function and the gut microbiota constitute the emerging concept of the gut–thyroid axis, providing a novel framework for understanding the disease. Microbiota-targeted interventions, including probiotics, prebiotics, synbiotics, and dietary modulation, have demonstrated potential to improve microbial composition, alleviate systemic inflammation, enhance thyroid hormone utilization, and reduce autoantibody levels. This review systematically explores the mechanistic links between gut microbiota and hypothyroidism, critically evaluates current microbiota-based therapeutic strategies, and highlights future opportunities for personalized, microbiome-driven interventions to optimize the management of hypothyroidism.